EXPAT 7 Countries Where $50,000 Is Enough to Retire (2026)
In this video, we break down 7 countries where $50,000 in savings — paired with Social Security — gives everyday Americans a genuine path to retiring abroad. Not a vacation. Not a trial run. A full retirement on a fixed income. We run every destination through our Senior Stability Index: warmth, Social Security math, and visa stability. And for every country on this list, we expose the trap hiding inside before you book a one-way flight.